2016
DOI: 10.1038/srep38672
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric polymer gated OFET: Cutting-edge electro-mechanical transducer for organic MEMS-based sensors

Abstract: The growth of micro electro-mechanical system (MEMS) based sensors on the electronic market is forecast to be invigorated soon by the development of a new branch of MEMS-based sensors made of organic materials. Organic MEMS have the potential to revolutionize sensor products due to their light weight, low-cost and mechanical flexibility. However, their sensitivity and stability in comparison to inorganic MEMS-based sensors have been the major concerns. In the present work, an organic MEMS sensor with a cutting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Apart from utilizing a single piezoelectric material as a transducer, combination with a piezoelectric material and an amplifier element, such as a dual-gate (DG) OFET, can also be used to build flexible pressure sensors with improved sensitivity. 98 Kim et al 99 presented the precise detection of unknown and small amount of stimuli for both dynamic and static pressures by measuring output signals from an OFET platform with highly sensitive microstructured functional gate dielectrics ( Figures 13A and 13B). Because of the larger flexoelectricityenhanced piezoelectric effects in pyramidal microstructures, organic piezoelectric material poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)) greatly improved the responsivity of the OFET sensor to detect pressures as low as 20 Pa.…”
Section: Ofet-based Capacitive-type Pressure Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from utilizing a single piezoelectric material as a transducer, combination with a piezoelectric material and an amplifier element, such as a dual-gate (DG) OFET, can also be used to build flexible pressure sensors with improved sensitivity. 98 Kim et al 99 presented the precise detection of unknown and small amount of stimuli for both dynamic and static pressures by measuring output signals from an OFET platform with highly sensitive microstructured functional gate dielectrics ( Figures 13A and 13B). Because of the larger flexoelectricityenhanced piezoelectric effects in pyramidal microstructures, organic piezoelectric material poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)) greatly improved the responsivity of the OFET sensor to detect pressures as low as 20 Pa.…”
Section: Ofet-based Capacitive-type Pressure Sensorsmentioning
confidence: 99%
“…Consequently, highly sensitive pressure sensors with relative current change of 155 versus a pressure load of 300 kPa and a low operation voltage of À5 V were demonstrated. Furthermore, Thuau et al 98 reported an organic micro electro-mechanical system (MEMS) sensor with a cutting-edge electro-mechanical transducer consisting of P(VDF-TrFE) piezoelectric polymer as the active gate dielectric ( Figures 13E and 13F). Such an advanced scheme and poling process enabled highly efficient integrated electro-mechanical transduction for physical and humidity sensing applications.…”
Section: Ofet-based Capacitive-type Pressure Sensorsmentioning
confidence: 99%
“…Stable and robust natures of silicon-based materials, however, may result in limited responses upon the change of external stimuli such as temperature [9] and pressure and require additional responsive materials coated or deposited for capturing specific targets. Materials used in seminal exemplary works include SU-8 photoresist, [14][15][16][17][18] polystyrene, [19] polyimide, [20] polymethylmethacrylate (PMMA), polycarbonate (PC), [21] polypropylene, polyvinylidenfluoride, [22] poly(L-lactide), [23] hexanediol diacrylate, [24] poly(vinylidenefluoride/trifluoroethylene), [25] polyethylene terephthalate, [26] and polydimethylsiloxane (PDMS). Therefore, many researchers have been naturally seeking alternative materials to make resonators used for sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…For pressure/force/strain detection they exploit the piezoresistive effect [2][3][4], the piezoelectric effect [5][6][7][8] or capacitive changes [9,10], whereas for temperature sensing capacitive [11] and pyroelectric-based sensors [12] can be found.…”
Section: Introductionmentioning
confidence: 99%
“…To harvest the response of certain materials to pressure/force/strain or temperature stimuli, the sensors often contain field-effect transistors (FETs) that convert the response generated by the material to an amplified voltage signal, suitable for subsequent interfacing with readout electronics [4,7,8,[13][14][15][16][17][18][19]. Here, ferroelectric polymers are very attractive because they exhibit piezo-and pyro-electric properties, while being inherently compatible with plastic substrates.…”
Section: Introductionmentioning
confidence: 99%